Non-destructive beam cross-section detector at the MMFL LEBT - Esin, S.K; Nikulin, E.S.; Rezvov, V.A.; Ioudin, L.I.; Yakushev, V.P (Вопросы атомной науки и техники, 2004)
The maiden outcomes of a television application for monitoring on the MMFL Proton Injector beam parameters are adduced. In the basis of a system it is non-interrupted ionization detector reshaping the beam cross-section image. The system provides rendition of cross-section and storage information, allows controlling the density distribution, its vertical and horizontal profiles and their width as well as position of the beam main point. The capability of temporary parameters diagnostics are beam structure shape and extension is simultaneously afforded.